Integrating Quality of Life in the Care Pathway of Cancer Patients Undergoing Immunotherapy Treatment: Descriptive, Cross-sectional Survey of an Online Patient Community's Experiences and Expectations - Ophélie Wilczynski; Anthony Boisbouvier; Lise Radoszycki; François-Emery Cotté; Anne-Françoise Gaudin; Hervé Lemasson (JMIR Publications, 2022)
BackgroundNew cancer treatments, such as immune checkpoint inhibitors (ICIs), can improve survival and health-related quality of life (HRQoL) in patients with cancer. Although long-term monitoring of HRQoL has been shown to improve survival, integration of HRQoL into everyday practice remains poorly documented. ObjectiveThis study describes experiences and expectations of patients treated with ICIs regarding a discussion of HRQoL with health care professionals (HCPs) in cancer management. MethodsThis cross-sectional study was conducted in an online patient community (Carenity) in France. Patients treated with ICIs for cancer, included between September 2018 and January 2019, completed a questionnaire to assess the involvement of HCP in a discussion of HRQoL and when and what was discussed. ResultsOf 82 patients included (mean age: 56.9 years, 95% CI 54.2-59.6; 46 [56%] male; 34 [41%] with lung cancer), 62 (76%) reported discussing HRQoL at least once with HCPs, mainly general practitioners (54/82, 66%), oncologists (53/82, 65%), and hospital nurses (50/82, 61%). Around half (45/82, 55%) of the patients were satisfied with these discussions. Discussions with the oncologist were at the patient's initiative (34/53, 64%). Discussions occurred primarily during follow-up visits (40/62, 65%), when adverse events occurred (30/62, 48%), and at treatment initiation (27/62, 32%). The most discussed dimensions were symptoms (48/62, 77%) and physical well-being (43/62, 69%). With respect to expectations, 54/82 (66%) patients considered oncologists as the most important HCPs for discussing HRQoL. These discussions were desirable throughout the care pathway, particularly at diagnosis (63/82, 77%) and when treatment was initiated (75/82, 92%) or changed (68/82, 83%). All HRQoL dimensions were considered important to discuss. ConclusionsWith only around half of the patients satisfied with HRQoL discussions, impactful HRQoL integration in clinical practice is critical. According to patients, this integration should involve mainly oncologists and general practitioners, should happen at every step of the care pathway, and should be extended to dimensions that are currently rarely addressed.